Key Questions in Considering a Value-Added Tax for Central and Eastern European Countries - Cnossen, Sijbren (IMF Working Papers; Working Paper ;, 1991)
In the course of introducing a market-oriented tax system, most Central and Eastern European countries are actively considering the merits of a value-added tax (VAT). This paper examines a wide range of social, economic, structural, and administrative issues that are pertinent to the introduction of a VAT. These issues have regard to the burden distribution of the VAT, its effect on the price level and economic growth, as well as the coverage of the tax, the definition of the base, and the choice of the rate structure. Various legal and administrative aspects are also reviewed. The paper draws on the experience with value-added taxation of the member states of the European Community (EC) and other countries that belong to the Organisation for Economic Cooperation and Development (OECD).